2015
DOI: 10.1038/nchembio.1859
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological targeting of the Wdr5-MLL interaction in C/EBPα N-terminal leukemia

Abstract: The CEBPA gene is mutated in 9% of patients with acute myeloid leukemia (AML). Selective expression of a short 30 kDa C/EBPα translational isoform, termed p30, represents the most common type of CEBPA mutations in AML. The molecular mechanisms underlying p30-mediated transformation remain incompletely understood. We show that C/EBPα p30, but not the normal p42 isoform, preferentially interacts with Wdr5, a key component of SET/MLL histone-methyltransferase complexes. Accordingly, p30-bound genomic regions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
286
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 241 publications
(322 citation statements)
references
References 59 publications
10
286
0
Order By: Relevance
“…The findings of MLL being phosphorylated and activated by ATR in order to allow for full activation of the S-phase checkpoint further highlight the functional interplay between oncogene-induced DDR and COMPASS complex (Liu et al, 2010). Our preliminary experiments with two available low potency WDR5 inhibitors supported the centrality of the WDR5 network (OICR-9429), more than MLL-specific associations (MM-401), in driving PDAC cell proliferation, but also highlighted the requirement for a new generation of potent and selective Myc-oriented WDR5 inhibitors to deeply dissect the WDR5-Myc molecular dynamics and accelerate the bench-tobedside translation process (Grebien et al, 2015;Cao et al, 2014). In further support of our mechanistic findings, it was previously demonstrated that ATR inhibition sensitizes PDAC cell lines to radiation or chemotherapy (Prevo et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…The findings of MLL being phosphorylated and activated by ATR in order to allow for full activation of the S-phase checkpoint further highlight the functional interplay between oncogene-induced DDR and COMPASS complex (Liu et al, 2010). Our preliminary experiments with two available low potency WDR5 inhibitors supported the centrality of the WDR5 network (OICR-9429), more than MLL-specific associations (MM-401), in driving PDAC cell proliferation, but also highlighted the requirement for a new generation of potent and selective Myc-oriented WDR5 inhibitors to deeply dissect the WDR5-Myc molecular dynamics and accelerate the bench-tobedside translation process (Grebien et al, 2015;Cao et al, 2014). In further support of our mechanistic findings, it was previously demonstrated that ATR inhibition sensitizes PDAC cell lines to radiation or chemotherapy (Prevo et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…The small-molecule OICR9429 has recently been shown to block the interaction of WDR5 with MLL and its protein-protein interaction network (33). We performed protein coimmunoprecipitation assays and confirmed that treatment with OICR9429, compared with its negative control compound OICR0547, blocked the formation of WDR5-N-Myc protein complex (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 71%
“…WDR5, a core component of the histone H3K4 methyltransferase complex, is crucial for vertebrate development and plays an important role in the self-renewal of pluripotent cells and cell differentiation (39,55). Multiple studies have recently documented that dysregulated WDR5 is involved in promoting cancer metastasis and chemoresistance (56,57), suggesting that WDR5 may serve as a therapeutic target for cancer (58). However, WDR5 is extensively expressed in numerous cell types and plays important roles in various biological functions (39,55,59,60).…”
Section: Blockage Of Vegf-c Reverses Blacat2-induced Ln Metastasis Inmentioning
confidence: 99%